Review of Slice Resource Management Technology in Space-Integrated-Ground Access Network - Ning HUI; Qian SUN; Yuanyuan WANG; Zongshuai ZHANG; Lin TIAN; Jing ZHANG; Xiao WEI (天地一体化信息网络)
With the explosive growth of diff erentiated services, it is urgent to manage wireless spectrum and computing resources on demand dynamically in the sliced access network (RAN) of the space-integrated-ground network.Resulting from that, refi ned and guaranteed qualities of services are achieved.Thus, it is necessary to study the dynamic management of spectrum and computing resources in the sliced RAN of space-air-ground integrated networks.The resource management technologies in sliced RAN of the space-integrated-ground were discussed.The current research status of resource management in the space-integratedground access network was summarized.The future demands of resource management in sliced RAN of the space-integratedground system were analyzed, included the high isolation of wireless spectrum resource, the collaboration of computing resources among space and ground parts, and the real-time heterogeneous resource management in complex sliced RAN of space-air-ground integrated networks.The corresponding key technologies of the three demands were provided.